2022
DOI: 10.3390/vaccines10020148
|View full text |Cite
|
Sign up to set email alerts
|

The Highly Productive Thermothelomyces heterothallica C1 Expression System as a Host for Rapid Development of Influenza Vaccines

Abstract: (1) Influenza viruses constantly change and evade prior immune responses, forcing seasonal re-vaccinations with updated vaccines. Current FDA-approved vaccine manufacturing technologies are too slow and/or expensive to quickly adapt to mid-season changes in the virus or to the emergence of pandemic strains. Therefore, cost-effective vaccine technologies that can quickly adapt to newly emerged strains are desirable. (2) The filamentous fungal host Thermothelomyces heterothallica C1 (C1, formerly Myceliophthora … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Several studies have demonstrated the bene ts of C1 produced proteins as promising vaccine candidates for various viral pathogens such as In uenza A virus, SARS-CoV-2, and orthobunyaviruses. These studies have used different subunits, such as the hemagglutinin for In uenza A virus, the RBD for SARS-CoV-2 and part of the Gc glycoprotein for Schmallenberg virus 18,19,23 . A previous study testing C1-derived SARS-CoV-2 RBD protein in rabbits for toxicology did not show any local or systemic side effects of fungal produced proteins, indicating its potential safety for use in humans 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the bene ts of C1 produced proteins as promising vaccine candidates for various viral pathogens such as In uenza A virus, SARS-CoV-2, and orthobunyaviruses. These studies have used different subunits, such as the hemagglutinin for In uenza A virus, the RBD for SARS-CoV-2 and part of the Gc glycoprotein for Schmallenberg virus 18,19,23 . A previous study testing C1-derived SARS-CoV-2 RBD protein in rabbits for toxicology did not show any local or systemic side effects of fungal produced proteins, indicating its potential safety for use in humans 24 .…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, the C1 expression system has been genetically modi ed continuously resulting in a well-characterized genetic toolbox and technology platform 17 . Besides the industrial use, heterologous proteins expressed by the C1 expression system have been successfully used such as the successful production of SARS-CoV-2 Full Spike protein, receptor binding domain (RBD)-based vaccine candidates against COVID-19 and hemagglutinin and neuraminidase in uenza antigens in animal models, showing their immunogenicity and effectiveness [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…The expression vector was transformed into C1 DNL-155 strain as described and cell clones producing RBD-C-tag protein were selected. 14 …”
Section: Methodsmentioning
confidence: 99%
“…C1-RBD was manufactured in a 10-L Bioflo 120 Fermenter (Eppendorf, Hamburg). Five liters of high concentration yeast extract medium with glucose 14 was inoculated with a seed culture of 500 ml the C1 DNL-155 production strain, Fermentation conditions were as decribed. 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation